Non-Hodgkin lymphoma of bone in an HIV-infected patient from Argentina - Uriel Sandkovsky; Pablo Fernando Martin; Emiliano Bissio (Journal of Infection in Developing Countries)
Introduction: Human immunodeficiency virus (HIV)-infected patients are at higher risk for development of Non-Hodgkin's lymphoma (NHL). The estimated incidence of NHL in patients with acquired immunodeficiency syndrome (AIDS) is much higher when compared to the general population. Most AIDS-associated NHL are of intermediate- or high-grade B-cell type and involve extranodal sites more frequently. The most common sites are the central nervous system (CNS), gastrointestinal tract, liver, bone marrow and soft tissues.